Vibrational spectra of sodium paratungstate 26 hydrate, Na10(H2W12O42)·26H2O - George, B. L. (1992)
A great number of polymolybdates and tungstates have been identified and subjected to a series of investigations. These types of compounds are interesting in several fields of chemistry including catalysis, solid-state applications and medicine [4-6]. X-ray studies of these phases show the existence of corner- and edge-shared XO6 octahedra (X = Mo and W).